Procurement 20/20 : supply entrepreneurship in a changing world - Spiller, Peter, 1972- (John Wiley & Sons, Inc., 2014)
How to achieve procurement excellence today and evolve to be ready for tomorrow Procurement entrepreneurship pays. High-performing procurement teams can deliver huge value to their companies-regardless of industry. The best companies are advancing talent-management strategies into the heart of their procurement organizations with huge success. In addition to an estimated 84 billion in yearly cost savings, companies who give procurement leaders prominence deliver superior returns from their operations as well as lower their costs of goods sold. This book, written by a group of p.